Notulae ad floram Sloveniae - Dakskobler, Igor (Hladnikia (Ljubljana), 1996)
New localities in western part of distribution area (sub-Mediterranean and prae-Alpine region of Slovenia)
Keywords: fitogeografija; flora; florae; phytogeography; Slovenia; Slovenija; vegetacija; vegetation